Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pone.0234985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TSH on Non-Alcoholic Fatty Liver Disease (NAFLD) independent of obesity in children of predominantly Hispanic/Latino ancestry by causal mediation analysis

Abstract: Background Nonalcoholic Fatty Liver Disease (NAFLD) is a common co-morbidity of obesity. Elevated TSH levels (eTSH), also associated with obesity, may contribute to the dysmetabolic state that predisposes to NAFLD.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Recently, another study [15] reported a strong link between TSH level and NAFLD proved by biopsy, independent of obesity, suggesting that thyroid hormone directly affect the synthesis and metabolism of cholesterol and fatty acids in an autonomous way by regulating the transcription of target genes involved in liver metabolism. However, our study failed to show statistical significance between ALT and TSH levels in lean PCOS, perhaps owing to the normal range of TSH levels in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, another study [15] reported a strong link between TSH level and NAFLD proved by biopsy, independent of obesity, suggesting that thyroid hormone directly affect the synthesis and metabolism of cholesterol and fatty acids in an autonomous way by regulating the transcription of target genes involved in liver metabolism. However, our study failed to show statistical significance between ALT and TSH levels in lean PCOS, perhaps owing to the normal range of TSH levels in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies [ 12 , 13 ] suggest that higher TSH level is also correlated with metabolic syndrome in PCOS; Emel et al [ 14 ] revealed that obese children demonstrate an increase in TSH levels as the degree of hepatic steatosis increased. Recently, another study [ 15 ] reported a strong link between TSH level and NAFLD proved by biopsy, independent of obesity, suggesting that thyroid hormone directly affect the synthesis and metabolism of cholesterol and fatty acids in an autonomous way by regulating the transcription of target genes involved in liver metabolism. However, our study failed to show statistical significance between ALT and TSH levels in lean PCOS, perhaps owing to the normal range of TSH levels in our study.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is considered to possess a complex trait resulting from environmental exposures and multiple susceptible genes. Our study is the first research to explore the correlation and causal mediation between TG level and NAFLD in Chinese elderly group even though the mediation effect in our study is not as high as that in Nichols, P. H. et al result - the mediated effect of TSH on NAFLD was 16.0% [ 38 ]. Our mediation analysis showed that TG played a partial mediating role in the relationship between rs1260326 and NAFLD.…”
Section: Discussionmentioning
confidence: 69%
“…The rs626283 polymorphism in the MBOAT7 gene has been associated with MASLD in adults, which is believed to be due to increased intrahepatic triglyceride content and inflammation. A study published in 2018 investigated this association within a multiethnic cohort of obese children and adolescents and found that this rs626283 variant in the MBOAT7 gene was associated with MASLD in non-Hispanic White obese children and adolescents but not among Hispanic and Black children and youth, thus showing genetic variation at the pediatric level that does not exist at the adult level [55] .…”
Section: Genetic Studies Investigating Masld In Pediatric Populationsmentioning
confidence: 99%